2003
DOI: 10.1088/0953-8984/15/23/301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of confining walls on the interaction between particles in a nematic liquid crystal

Abstract: We investigate theoretically how the confining walls of a nematic cell affect the interaction of particles mediated by the elastic deformation of a nematic liquid crystal. We consider the case where strong homeotropic or planar anchoring is imposed on the flat parallel walls so that the director on the wall surfaces is fixed and uniform alignment is achieved in the bulk. This set-up is more realistic experimentally than any other previous theoretical studies concerning the elastic-deformation-mediated interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Consideration of finite anchoring effects in colloidal nematostatics requires incorporation of a finite-size source, and theories, based on the approximation of point-like sources, encounter difficulties. For instance, the treatment of finite anchoring in [61,62], based on the approach [43,44,63], required an introduction of an artificial director field inside the colloids' material. In our approach, the anchoring effects can be easily included.…”
Section: Incorporation Of Real Surfaces and Finite Anchoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of finite anchoring effects in colloidal nematostatics requires incorporation of a finite-size source, and theories, based on the approximation of point-like sources, encounter difficulties. For instance, the treatment of finite anchoring in [61,62], based on the approach [43,44,63], required an introduction of an artificial director field inside the colloids' material. In our approach, the anchoring effects can be easily included.…”
Section: Incorporation Of Real Surfaces and Finite Anchoringmentioning
confidence: 99%
“…As in electrostatics, these effects can be addressed by introducing image-multipoles behind the confining surface [59][60][61][62][63]. The image method for finite-size colloids [59,60] is presented in section 3.4.…”
Section: -7mentioning
confidence: 99%
“…If both particles have the same height h = h ′ then ρ = r and ϕ = θ. In this case the dipole-dipole energy of interaction (27) between two parallel dipoles at the same height h near the wall with planar anchoring conditions ( Fig.8.a) can be presented as: Let's analyze dipole-dipole interaction (31) which corresponds to the usual dipole configuration on the Fig.8.a. First remarkable behavior is the dipole-dipole isotropic attraction on far distances.…”
Section: Interaction Between Two Particles Near One Planar Wallmentioning
confidence: 99%
“…Authors received formula similar to (46) but with unknown multiplier Γ and without the constant 3πKβ 2 a 6 L 5 ζ(5). If we set Γ = 2πKc = −2βπKa 3 in [27] we receive the same formula (46) up to a constant.…”
Section: Interaction Of the One Particle With Nematic Cellmentioning
confidence: 99%
“…In that paper authors have found exponential screening effects for quadrupole-quadrupole interaction between spherical particles in homeotropic NLC cell. From our viewpoint there was only one theoretical approach for description of colloidal particles in confined NLC performed in papers [13,14].In this paper we propose the new approach for quantitative description of the axial colloidal particles in confined NLC. This method enables to find self energy of one colloidal particle and interaction energy between two particles in arbitrary confined NLC with strong anchoring condition n µ (s) = 0 on the bounding surface.…”
mentioning
confidence: 99%